North-South Migration and Problems of Migrant Traders in Agbogbloshie (African Human Mobility Review, 2021)
In this paper, the problems of labour migrants in their destination areas will beinvestigated, owing to the need for a deeper understanding of their specificlivelihood problems in these areas. Using a mixed method approach to datacollection, 100 migrant traders in Agbogbloshie, in the south industrial area ofAccra, were interviewed about their livelihood problems. The data analysedrevealed that the majority of labour migrants were not formally educated andwere primarily involved in the trading of consumables. Additionally, conflict,poverty, decline in agriculture productivity and unavailability of social amenitieswere important factors that influenced their north-south migration in Ghana.Furthermore, inability to access credit facilities, theft of migrant traders’ wares,discrimination against migrants, exploitation of migrants by market leaders andharassment by city authorities were some of the problems that migrant tradersfaced. Dependent on these findings, to effectively minimise these problems, it issuggested that migrant traders should unionise as this can help them accesscredit from formal financial institutions. It would also present migrants with acommon voice to engage in dialogue with city authorities on the appropriateways of managing their activities in the market.